Prevalence and Treatment of Dysphonia in Parkinson's Disease: A Cross‐Sectional National Database Study - Vicki Liu; Dori Smith; Helena Yip (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objective Around 89% of individuals with Parkinson's disease (PD) present with speech and voice disorders, but only 3%–4% receive speech treatment. Using the NIH All of Us Research Program, this study aims to report the prevalence of dysphonia, the incidence of speech evaluations and treatments, and potential disparities in PD patients on a national scale. Methods ICD‐9 and ICD‐10 codes were used to identify individuals with PD and dysphonia in the All of Us database. Diagnostic voice care was determined using CPT codes for flexible laryngoscopy and speech evaluation, while treatment was based on CPT codes for vocal fold augmentation and speech therapy. Unadjusted and adjusted logistic regression analyses were conducted to evaluate the association between voice care access and demographic and socioeconomic factors. Results Of 1968 PD patients, 257 (13.1%) had a concomitant diagnosis of dysphonia. 1683 patients (85.5%) received no voice care. Among those with voice care, 264 (13.4%) underwent a diagnostic evaluation and 124 (6.3%) received treatment. Based on adjusted logistic regression models, factors associated with decreased odds of voice care were female sex (aOR = 0.62, 95% CI = 0.45–0.85, p = 0.004) and Hispanic ethnicity (aOR = 0.44, 95% CI = 0.22–0.90, p = 0.02). Conclusion PD commonly presents with voice disorders. Using a national database, only 13.1% of PD patients had a formal dysphonia diagnosis, and only 6.3% received speech treatment. Female sex and Hispanic ethnicity correlated with decreased voice care. This study suggests the underdiagnosis and undertreatment of dysphonia in PD. Level of Evidence: 3.